Insumos no PIS/COFINS: método pragmático - Favacho, Fernando Gomes (2015)
The question studied in this work is the definition of inputs used on the non-cumulativity system in the Brazilian Social Securuty Contributions (named PIS/COFINS). We start this study using a method of defining objects by it's conceivable effects, namely the Peirce´s pragmaticism, wherein the construction of the concept evolves and is connected to its conceivable consequences. The work demonstrates the evolution of concepts through judicial decisions. The doctrine and previous administrative court trend decisions states that the "non-cumulative" PIS/COFINS, unlike the non-cumulative system of the Industrialized Products Tax (IPI), uses tax credits from inputs used not only directly in the product, with the physical wear, but also as other items used for the fulfillment of production. Through jurisprudential research, particularly in the courts aimed at stability trials, we have the content needed to create a prognosis to show us how to draw the formation of a habit when it comes to applying the concept of inputs at article 3, item II of the Brazilian Federal Law 10,627/2002 and 10,833/2003.The hypothesis created by abductive method, that is, through the repeated decisions, refutes the restrictive vision of the Federal Revenue of Brazil manifested on the Normative Instructions 247/2002 and 404/2004 and legal consultations answered by the Brazilian Federal Revenue Office in that coincides the inputs used by IPI. In a rare decision, the Administrative Board of Tax Appeals equates the concept to costs and expenses deductible for Corporate Income Tax, whereas in others - today majority position searches its own concept. In these, the idea of inputs is focused on the use of inputs for the production or service, which in our view is an application of the pragmatic maxim. The case brings us a prospect, a conjecture from the facts. The conclusion, therefore, is a prognosis. We will have here the possibility to see inputs as a general clause to be determined by the case. The conclusive prognosis makes the fact itself a part of the norm composed by the judge